1974
DOI: 10.1113/jphysiol.1974.sp010500
|View full text |Cite
|
Sign up to set email alerts
|

The hippocampal control of neuronal discharges in the septum of the rat

Abstract: SUMMARY1. Records of field potentials and of the firing patterns of single neurones evoked by stimulation of the fimbria and fornix have been obtained from the septal nuclei of the rat.2. Fimbrial stimulation caused orthodromic activation of lateral septal neurones which was followed by a lengthy inhibition. In the medial septum such stimulation could elicit an antidromic response; but inhibition whose duration depended upon whether the neurones were firing irregularly or in synchronized bursts was obtained wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(73 citation statements)
references
References 19 publications
7
66
0
Order By: Relevance
“…This is consistent with experimental evidence suggesting that activity in region CA1 and region CA3 can inhibit activity in the medial septum, and thereby downregulate cholinergic modulation [105]. This allowed the network to respond initially to patterns with dynamics set by strong cholinergic modulation, suppressing the autoassociative and hetero-associative function of excitatory connections.…”
Section: Feedback Regulation Of Cholinergic Modulationsupporting
confidence: 74%
“…This is consistent with experimental evidence suggesting that activity in region CA1 and region CA3 can inhibit activity in the medial septum, and thereby downregulate cholinergic modulation [105]. This allowed the network to respond initially to patterns with dynamics set by strong cholinergic modulation, suppressing the autoassociative and hetero-associative function of excitatory connections.…”
Section: Feedback Regulation Of Cholinergic Modulationsupporting
confidence: 74%
“…This node controlled the release of acetylcholine (ACh) in all modelled layers. The node itself received input from the septal y oscillator, and from hippocampal interneurons (Dragoi et al, 1999;McLennan and Miller, 1974; Tóth et al, 1993). The latter connections were inhibitory; in essence, the cholinergic node was disinhibited only when entorhinal input did not elicit any recall in the hippocampus; that is, when the input was new.…”
Section: Modelmentioning
confidence: 99%
“…These hippocampo-septal projection cells receive convergent input from large numbers of hippocampal principal cells (Tóth et al, 1993). Hippocampal activity may thus inhibit the septum; indeed, both fimbria stimulation (McLennan and Miller, 1974) and hippocampal sharp waves (Dragoi et al, 1999) were shown to inhibit neuronal activity in the medial septum.…”
Section: Acetylcholine and Learning Dynamicsmentioning
confidence: 99%
“…In this respect it is noteworthy that the few studies addressing the function of the hippocampo-medioseptal pathway were performed in anaesthetized rats, and did not characterize the neurons responding to hippocampal input (McLennan and Miller, 1974;Dragoi et al, 1999). Moreover, the clearest effects of hippocampal influence on septal activity were observed during hippocampal sharp waves, rather than REM-associated theta (Dragoi et al, 1999).…”
mentioning
confidence: 99%